2006
DOI: 10.1007/s10549-006-9380-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered frontocortical, cerebellar, and basal ganglia activity in adjuvant-treated breast cancer survivors 5–10 years after chemotherapy

Abstract: Specific alterations in activity of frontal cortex, cerebellum, and basal ganglia in breast cancer survivors were documented by functional neuroimaging 5-10 years after completion of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
237
0
14

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(273 citation statements)
references
References 65 publications
22
237
0
14
Order By: Relevance
“…Women treated with chemotherapy showed a significantly altered blood flow in several brain areas and abnormal activation in the inferior frontal cortex dur- ing a short-term memory recall task compared to healthy control women [38]. MTX is also known to cause structural damage to blood vessels, as measured with elevated levels of circulating endothelial cells in mice after intraperitoneal injections of MTX [43], and elevated apoptosis markers in cultured bovine pulmonary artery endothelial cells after exposure to therapeutic levels of MTX [22].…”
Section: Introductionmentioning
confidence: 99%
“…Women treated with chemotherapy showed a significantly altered blood flow in several brain areas and abnormal activation in the inferior frontal cortex dur- ing a short-term memory recall task compared to healthy control women [38]. MTX is also known to cause structural damage to blood vessels, as measured with elevated levels of circulating endothelial cells in mice after intraperitoneal injections of MTX [43], and elevated apoptosis markers in cultured bovine pulmonary artery endothelial cells after exposure to therapeutic levels of MTX [22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using neuroimaging techniques in patients receiving chemotherapy have found structural and functional changes in brain regions associated with cognitive functioning (Inagaki et al 2007;Saykin and Wishart 2003). For example, positron emission tomography of breast cancer survivors revealed significant alterations in cerebral blood flow and in resting glucose metabolism in the frontal cortex and the cerebellum that were correlated with impairments in short-term memory recall tasks (Silverman et al 2007). Similarly, magnetic resonance imaging scans of breast cancer survivors showed reduced volume in various brain regions associated with cognitive function, and these changes were correlated with impaired performance on the attention/concentration and visual memory indices of the Wechsler Memory Scale-Revised or in working memory tasks (Inagaki et al 2007;Saykin et al 2006;Stemmer et al 1994).…”
mentioning
confidence: 99%
“…Algunos datos sostienen que el deterioro cognitivo detectado por las imágenes de resonancia magnética se correlacionan con el deterioro cognitivo percibido pero no con los resultados de los test clásicos (46) ; también se objetiva más hipertensión en la sustancia blanca, y mayor extensión de actividad cerebral en la realización de una tarea de memoria (45) y menor sustancia gris y blanca en los giros prefrontal, parahipocampal y cingulado en las mujeres que sufrieron cáncer de mama tratadas con quimioterapia (47) . De igual forma, mediante resonancia magnética se han encontrado daños en la actividad del córtex frontal, el cerebelo y los ganglios basales en mujeres de cáncer de mama que habían recibido quimioterapia hacía 5-10 años (48) ; la quimioterapia puede afectar a la sustancia blanca del cuerpo calloso (49) y a la sustancia gris cortical (50) . Mediante encefalograma, se observan alteraciones electrofisiológicas en los potenciales P3 en personas con cáncer de mama tratadas con dosis altas de quimioterapia hacía 4 años (51) .…”
Section: Instrumentos Y Estrategias De Evaluación Del Rendimiento Cogunclassified